2019
DOI: 10.3802/jgo.2019.30.e90
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of progestin plus metformin as a fertility-sparing treatment for atypical endometrial hyperplasia and endometrial cancer patients

Abstract: ObjectiveThe present study investigated long-term outcomes of medroxyprogesterone acetate (MPA) plus metformin therapy in terms of control of atypical endometrial hyperplasia (AEH) and endometrial cancer (EC), and post-treatment conception.MethodsWe retrospectively analyzed 63 patients (42 with EC; 21 with AEH) who underwent fertility-sparing management using MPA plus metformin. MPA (400 mg/day) and metformin (750–2,250 mg/day) were administered to achieve complete response (CR). Metformin was administered unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(79 citation statements)
references
References 27 publications
2
76
1
Order By: Relevance
“…Metformin was suggested to combine with MPA based on several mechanisms of reversing progesterone resistance. Mitsuhashi et al [22] demonstrated that the combination of MPA and metformin had significantly better prognosis than MPA alone in the patients with endometrial hyperplasia or cancer (3-year relapse-free survival, 79.3% vs. 45.2%; p = 0.031). And this prognosis benefit of MPA and metformin combination over MPA alone was more prominent for obese patients (BMI ≥ 25 kg/m 2 ) than non-obese patients (BMI < 25 kg/m 2 ) through inhibiting the phosphatidylinositol 3-kinase (PI3K)-protein kinase B (AKT)-mTOR pathway by activating AMPK, a master regulator of cellular energy homeostasis AMPK and the PI3K-AKT-mTOR pathway is known as one of the most commonly dysregulated signaling pathways in endometrial cancer [23].…”
Section: Discussionmentioning
confidence: 99%
“…Metformin was suggested to combine with MPA based on several mechanisms of reversing progesterone resistance. Mitsuhashi et al [22] demonstrated that the combination of MPA and metformin had significantly better prognosis than MPA alone in the patients with endometrial hyperplasia or cancer (3-year relapse-free survival, 79.3% vs. 45.2%; p = 0.031). And this prognosis benefit of MPA and metformin combination over MPA alone was more prominent for obese patients (BMI ≥ 25 kg/m 2 ) than non-obese patients (BMI < 25 kg/m 2 ) through inhibiting the phosphatidylinositol 3-kinase (PI3K)-protein kinase B (AKT)-mTOR pathway by activating AMPK, a master regulator of cellular energy homeostasis AMPK and the PI3K-AKT-mTOR pathway is known as one of the most commonly dysregulated signaling pathways in endometrial cancer [23].…”
Section: Discussionmentioning
confidence: 99%
“…Ninety‐seven percent of patients treated with MPA and metformin (61/63) achieved CR within 18 months. In comparison with a historical control (24 patients) treated only with MPA, administration of metformin significantly reduced relapses . Relapse‐free survival at 3 years in patients with EC treated with MPA plus metformin and MPA alone was 79.7% and 43.0%, respectively ( P < 0.05).…”
Section: A New Strategy Of Fertility‐sparing Treatment Combined With mentioning
confidence: 91%
“…Relapse‐free survival at 3 years in patients with EC treated with MPA plus metformin and MPA alone was 79.7% and 43.0%, respectively ( P < 0.05). Metformin may be more efficacious for patients with BMI ≥ 25 kg/m 2 , as patients with BMI ≥ 25 kg/m 2 had significantly better prognoses than patients with BMI < 25 kg/m 2 (OR, 0.27; 95% CI, 0.08–0.88; P = 0.03) …”
Section: A New Strategy Of Fertility‐sparing Treatment Combined With mentioning
confidence: 99%
“…A meta-analysis revealed that metformin was associated with improved overall survival in EC patients [ 14 ]. Mitsuhashi et al [ 40 ] reported that a regimen of MPA with metformin elicited a better prognosis than treatment with MPA alone with respect to relapse-free survival. A gonadotropin-releasing hormone (GnRH) agonist combined with another agent also can be used.…”
Section: Treatment Efficacy and Primary Modalitymentioning
confidence: 99%